Predicting the 2000-m rowing ergometer performance from anthropometric, maximal oxygen uptake and 60?s mean power variables in national level young rowers - Cerasola, D.; Bellafiore, M.; Cataldo, A.; Zangla, D.; Bianco, A.; Proia, P.; Traina, M.; Palma, A.; Capranica, L. (Journal of Human Kinetics, 2020)
Many studies reported various relationships between 2000-m rowing performance and anthropometric as well as metabolic variables, however, little is known about 60-s mean power in elite youth athletes. The aim of this study was to develop different regression models to predict 2000-m rowing indoor performance time (t2000) using anthropometric variables, maximal oxygen uptake (VO2max) and mean power established during a 60-s all-out test (W60) in national elite youth rowers. Fifteen youth male Italian rowers (age: 15.7 ± 2.0 years; body height: 176.0 ± 8.0 cm; body mass: 71.2 ± 10.0 kg) performed an incremental maximal test, a 60-s all-out test and a 2000-m race simulation using a Concept2 rowing ergometer to assess VO2max, W60 and t2000, respectively. The relationships of all variables with t2000 were investigated through Pearson`s correlation. Multiple regression analyses were used to verify the best prediction model of 2000-m indoor rowing performance. The reliability of these models was expressed by R2 and the standard error of estimate. The results showed that t2000 was significantly correlated with all the examined variables, except for VO2max/body mass and age, and exhibited the significantly highest relationship with W60 (r = -0.943). The combination of anthropometric, VO2max and W60 variables was found to be the most reliable equation to predict t2000 (R2 = 0.94, SEE = 6.4). W60 measure should be considered when monitoring the rower`s capability to perform high-intensity phases, important during the race`s fast start and end. Not requiring expensive equipment and long duration, a 60-s all-out test could be considered a valuable tool for predicting 2000-m performance of elite youth rowers.